2021
DOI: 10.3390/su13116253
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Proactive Eco-Innovation and Firm Financial Performance: A Circular Economy Perspective

Abstract: Eco-innovation has gained considerable attention in the academic and corporate world due to its potential in mitigating a firm’s sustainability issues. Most previous studies focused on the reactive approaches of eco-innovation using primary data. This study mitigates the existing research gap by highlighting proactive eco-innovation and using a secondary panel dataset. The prime objective of this study is to investigate the relationship between proactive eco-innovation and firms’ financial performance. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 44 publications
(66 reference statements)
2
42
0
Order By: Relevance
“…According to Fernando [9], the right integration of ecoinnovation and business strategy should be easy to understand and, more importantly, usable by all corporate stakeholders while increasing firm capabilities and minimising negative environmental effects during the manufacturing process. Eco-innovation activities were expanded during the COVID-19 pandemic [35]. Eco-innovation is expressed in Malaysia through the concept of green technology, and by combining the innovation process and technology into their business model, organisations can achieve long-term survival while simultaneously competing more effectively in the market [13].…”
Section: Eco-innovation Capabilitiesmentioning
confidence: 99%
“…According to Fernando [9], the right integration of ecoinnovation and business strategy should be easy to understand and, more importantly, usable by all corporate stakeholders while increasing firm capabilities and minimising negative environmental effects during the manufacturing process. Eco-innovation activities were expanded during the COVID-19 pandemic [35]. Eco-innovation is expressed in Malaysia through the concept of green technology, and by combining the innovation process and technology into their business model, organisations can achieve long-term survival while simultaneously competing more effectively in the market [13].…”
Section: Eco-innovation Capabilitiesmentioning
confidence: 99%
“…Researchers have found that those firms with a high level of innovation activities and capabilities gain better responses from the environment and obtain a competitive advantage to enhance their performance [2,16,20]. Various scholars and researchers stressed that one of a firm's vital resources is innovation, as it has a significant effect on a firm's performance [4,[42][43][44]. Robust findings show a significant and positive relationship between innovation and firm performance [4,[44][45][46].…”
Section: Innovationmentioning
confidence: 99%
“…For example, Johl S.K. and Toha [35] performed a study in 31 Malaysian public energy companies; Kiefer et al [36] carried out a similar study in Spain. The waste generation management problem is investigated by Magazzino et al [37] who proposed an experiment based on artificial neural networks to understand how to interact within a complex ecosystem such as between the environment and waste.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%